Experiencing multicultural awareness and affective polarization: A phenomenological inquiry - Mahfud Anshori; Chatarina Heny Dwi Surwati (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
This study examines how Generation Z students experience multicultural awareness and navigate affective polarization in both everyday life and digital spaces. Using a Heideggerian phenomenological design, it explores how students emotionally respond to cultural, ethnic, and religious differences encountered in their social interactions. Participants were purposively selected from a culturally diverse university in Surakarta, Indonesia, and interviewed in depth. Hermeneutic analysis reveals that students often face emotional ambivalence, tension, and fatigue when engaging with pluralism, leading them to adopt strategies such as emotional withdrawal, selective silence, or ethical self-restraint. At the same time, moments of empathy, recognition, and relational openness emerged as meaningful turning points. These findings show that polarization stems not only from ideological cleavages but also from lived emotional experiences. The study concludes that fostering emotional literacy and ethical reflection is essential in preparing young people to engage meaningfully with difference in increasingly plural and polarized societies.